Membangun Minat dan Jiwa Kewirausahaan Pada Siswa SMK Kartini Surabaya - Agustini, Ni Ketut Yulia; Indahwati, Indahwati; Kholidiah, Kholidiah (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
Building interest and entrepreneurial spirit in the younger generation is not easy, the perception that entrepreneurship is not an attractive or profitable career choice is one of the obstacles in building interest and developing an entrepreneurial spirit among young people, this perception causes young people's interest in entrepreneurship to still be very low. This service aims to provide entrepreneurship training in order to build economic independence for students at Vocational High School SMK Kartini 7 Surabaya. Generation Z is a generation that is expected to be able to contribute to participating in encouraging economic development and improving welfare, improving welfare starts for themselves, family, friends and the surrounding community. Inability to see business opportunities, lack of ideas or concepts, lack of knowledge and skills, fear of failure, inability to manage and face risks, lack of self-confidence, lack of support from people around them, all of these are factors that hinder the growth of interest and entrepreneurial spirit among the younger generation. For this reason, efforts are needed to overcome these obstacles, through entrepreneurship training. Entrepreneurship training aims to foster interest and build an entrepreneurial spirit among vocational school students and build awareness that entrepreneurship is very important to increase potential and self-development, build an independent, creative and innovative spirit, a tough generation that does not give up easily.